Mini Aquaponics System using IoT Technology for Teaching and Learning - Mohamad, Nur Syuhada; Zulazwi, Muhammad Luqman Danial; Mohd Razali, Muhammad Aiman; Ismet, Muhammad Izzat (Multidisciplinary Applied Research and Innovation, 2025)
Aquaponics is a farming method that integrates two elements namely aquaculture and hydroponics, which helps in growing healthy organic food with low use of chemical fertilizers. The Mini Aquaponics System using IoT Technology for Teaching and Learning is a project developed specifically for secondary school students for Form 2 in the subject Reka Bentuk dan Teknologi (RBT). This project offers a more effective learning system to help students understand more about what aquaponics is and how it works compared to traditional learning methods using textbooks and lectures. This project focuses on helping teachers and students learn interactively to make them more interested in aquaponics learning with the integration of Internet of Things (IoT) technology. In this project, there are two methods implemented which are the integration physical hardware of the aquaponics unit with IoT technology and the development of the web-based application for the e- Learning Management System (e-LMS). This Aquaponics System provides several courses in the e-LMS. Several sensors are involved to get input values from the aquaponics unit to monitors and display the aquaponics condition. The integration between IoT devices and the aquaponics system shows remarkable results to the ecosystem that can be monitored in real time from a monitoring dashboard. The collection of raw data from the monitoring results is very useful in implementing Artificial Intelligence (AI) to suggest maintenance required by Aquaponics System. On the other hand, this project is very helpful for students, teachers and all interested parties in understanding how aquaponics works, the monitoring process and the benefits of this cultivation method.